2001
DOI: 10.1002/ijc.1537
|View full text |Cite
|
Sign up to set email alerts
|

The copper-chelating agent, trientine, suppresses tumor development and angiogenesis in the murine hepatocellular carcinoma cells

Abstract: Angiogenesis is now recognized as a crucial process in tumor development, including hepatocellular carcinoma (HCC). Since HCC is known as a hypervascular tumor, antiangiogenesis is a promising approach to inhibit the HCC development. Trientine dihydrochloride (trientine) is used in clinical practice as an alternative copper (Cu)-chelating agent for patients with Wilson's disease of penicillamine intolerance. In our study, we examined the effect of Cu-chelating agents on tumor development and angiogenesis in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
119
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 40 publications
0
119
0
Order By: Relevance
“…2B), indicating that differential levels of copper intake affect the rate of cancer cell proliferation. Unrestricted growth of tumors depends on formation of new blood vessels, and copper has been shown to be involved in this process (5)(6)(7)(8). However, vascular density in tumors was not affected by copper status under our experimental conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B), indicating that differential levels of copper intake affect the rate of cancer cell proliferation. Unrestricted growth of tumors depends on formation of new blood vessels, and copper has been shown to be involved in this process (5)(6)(7)(8). However, vascular density in tumors was not affected by copper status under our experimental conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Serum copper levels are elevated in cancer patients and correlate with the severity of the disease and response to therapies (3,4). In animal models, copperchelating drugs have been reported to have antiangiogenic activity (5)(6)(7)(8). The molecular and cellular mechanisms by which copper levels modulate tumor angiogenesis and the generality of its effects on angiogenesis in different cancer types remain unclear, as are its potentially broader effects on tumor growth.…”
mentioning
confidence: 99%
“…Tumors are dependent on angiogenesis for their growth, invasion and metastasis (39)(40), and Cu plays an important role in this process. Due to the importance of angiogenesis and copper to tumor development, the use of copper chelators for antiangiogenic therapy has emerged as an interesting concept in cancer therapeutics (41)(42).…”
Section: Coppermentioning
confidence: 99%
“…Chelation of copper by TETA suppresses several angiogenic mediators, including vascular endothelial growth factor-1 (VEGF-1), fibroblast growth factor-1 (FGF-1), interleukin-1 (IL-1), IL-6, IL-8, and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB; refs. [9][10][11][77][78][79][80]. As a result, TETA exhibits antiangiogenic effects in tumor cells.…”
Section: Mechanism Of Action In Cancermentioning
confidence: 99%
“…It has also been suggested that TETA can be used in the treatment of cancer because it is a telomerase inhibitor (8), and has anti-angiogenesis properties (9)(10)(11), on the basis of preclinical investigations. In addition, a recent report showed that TETA treatment could overcome cisplatin resistance in human ovarian cancer cell culture via inhibition of superoxide dismutase 1/Cu/Zn superoxide dismutase (12).…”
Section: Introductionmentioning
confidence: 99%